# Algebra

posted by .

Multiplying sq rts
sqrt18a^7b times sqrt27a^8b^6

Jake 1214-
18 = 9 * 2 then sqrt 18 = 3sqrt2
sqrt a^7 = a^3 * sqrt a

27 = 9 * 3 then sqrt 27 = 3 sqrt3
sqrt a^8 = a^4
sqrt b^6 = b^3
Now just multiply the like-terms together.

3sqrt6 and sqrt2a^4?

• Algebra -

.. 3sqrt6 and sqrt2a^4?

So you simplified the problem first as I said above and you get:

3(a^3)sqrt(2a) * 3(a^4)(b^3)sqrt(3)

and then you multiply those 2 things together and you get:

9(a^7)(b^3)sqrt(6a)

## Similar Questions

l = lim as x approaches 0 of x/(the square root of (1+x) - the square root of (1-x) decide whether: l=-1 or l=0 or l=1 Let me make sure I understand the question. Do we have lim x->0 x/[sqrt(1+x) - sqrt(1-x)] ?
2. ### Inequality

When I solve the inquality 2x^2 - 6 < 0, I get x < + or - sqrt(3) So how do I write the solution?

4. ### math,algebra,help

Directions are simplify by combining like terms. x radiacal 18 -3 radical 8x^2 can someone show me how to do these types of problems. thanks I cant determine the second term. For the first, I think you meant x sqrt(18) which reduces …
5. ### Math

How do you find a square root of a number that's not a perfect square?
6. ### Mathematics

sqrt 6 * sqrt 8 also sqrt 7 * sqrt 5 6.92820323 and 5.916079783 So you can see the steps — sqrt 6 * sqrt 8 = sqrt 48 sqrt 7 * sqrt 5 = sqrt 35 I hope this helps a little more. Thanks for asking.